Analisis Potensi Bahaya Pada Pekerja Maintenance Kapal Di PT. X Kota Makassar - Lilis Widiastuti; Dian Rezki Wijaya; Ranti Ekasari; Muhammad Adam Izzulhaq (HIGIENE: Jurnal Kesehatan Lingkungan, 2020)
Every workplace has a risk of accidents. The amount of risk depends on the industry, technology, and the risk control efforts undertaken. HIRARC (Hazard Identification Risk Assessment and Risk Control)  is a way to identify the potential hazards that exist in each type of work. The steps begin with identifying the hazards, assessing the risks, and implementing controls. This study aimed to determine potential hazards, assess risks, and control risks to shipping maintenance workers at PT. X. This research was an observational study using a descriptive approach with the HIRARC concept method. The samples were laborers and a series of work processes in the ship maintenance section. Data were collected through observation, literature study, and documentation. The data were analyzed by descriptive statistics with a qualitative presentation. The results showed that 9 potential hazards and 27 risks were identified. The controls carried out were elimination, substitution, isolation, engineering, control administration, and personal protective equipment. This study concluded that each maintenance work area had the potential to experience an accident risk. The company should control the work area so it becomes protected from work accidents risk and occupational diseases. Keywords: HIRARC, hazard identification, risk assessment, risk control